Relationships between force-time curve variables and tennis serve performance in competitive tennis players - Fourel, L.; Touzard, P.; Fadier, M.; Arles, L.; Deghaies, K.; Ozan, S.; Martin, C. (The Journal of Strength and Conditioning Research, 2024)
Practitioners consider the role of the legs in the game of tennis as fundamental to achieve high performance. But, the exact link between leg actions and high-speed and accurate serves still lacks understanding. Here, we investigate the correlation between force-time curve variables during serve leg drive and serve performance indicators. Thirty-six competitive players performed fast serves, on 2 force plates, to measure ground reaction forces (GRF). Correlation coefficients describe the relationships between maximal racket head velocity, impact height, and force-time curve variables. Among all the variables tested, the elapsed time between the instants of maximal vertical and maximal anteroposterior GRF (r = -0.519, p < 0.001) and the elapsed time between the instant of maximal anteroposterior GRF and ball impact (r = -0.522, p < 0.001) are the best predictors of maximal racket velocity. Maximal racket head velocity did not significantly correlate with the mean or maximal vertical GRF or with the mean or maximum rate of vertical force development. The best predictor for impact height is the relative net vertical impulse during the concentric phase (r = 0.772, p < 0.001). This work contributes to a better understanding of the mechanical demands of tennis serve motion and gives guidelines to improve players preparation and performance. Trainers should encourage their players to better synchronize their upward and forward pushing action during the serve to increase maximal racket head velocity. Players should also aim to improve their relative net vertical impulse to increase impact height through strength training and technical instructions.